2016
DOI: 10.1590/1413-785220162401153984
|View full text |Cite
|
Sign up to set email alerts
|

Knee Arthroplasty Revision With a Constrained Implant Using Hinge and Rotating Tibial Basis

Abstract: Objective: To evaluate the results of total knee arthoplasty revisions performed in high complexity cases, with large bone defects or serious ligament deficiencies using a constrained implant hinge associated to a rotating tibial basis. Methods: We evaluated 11 patients in which we used the constrained implant hinge associated to rotating tibial basis, with minimum follow-up of two years. The indications for the procedure included instability, septic loosening, late postoperative infection without loosening an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 24 publications
(25 reference statements)
0
5
0
2
Order By: Relevance
“… 2 , 4 , 5 However, this type of implant is a valuable surgical option for cases of severe instability with ligament insufficiency, bone destruction of ligament insertions, fixed deformities, or asymmetry in the areas of flexion and extension that hinder proper balance. 2 , 7 , 9 The rotating-hinge design is desired, since it decreases the stress on the fixation and allows a more physiological movement of the knee. 4 , 6 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 2 , 4 , 5 However, this type of implant is a valuable surgical option for cases of severe instability with ligament insufficiency, bone destruction of ligament insertions, fixed deformities, or asymmetry in the areas of flexion and extension that hinder proper balance. 2 , 7 , 9 The rotating-hinge design is desired, since it decreases the stress on the fixation and allows a more physiological movement of the knee. 4 , 6 …”
Section: Discussionmentioning
confidence: 99%
“…Regarding previously available constrained implants, a single recent case series in Brazil reported a complication rate of around 70%, 9 considering major and minor complications, which discourages its use, even as the only option available to date for solving these cases. Therefore, the authors believe that the present study demonstrates the possibility of better results for this subgroup of patients with the present implant, when compared with implants previously available in Brazil.…”
Section: Discussionmentioning
confidence: 99%
“…The present study is one of the few found in the literature evaluating results from the use of constrained prostheses in the Brazilian and Latin American populations. 12,13 Contrary to the predicted hypothesis, the main finding was the observation that the use of constrained implants enables joint function and muscle strength comparable to that of patients who underwent primary arthroplasty using conventional implants with posterior stabilization. In our sample, the average functional KSS was 69.80 points in the Hinge group, not statistically different from the 74.23 points observed in the control group; we also found no differences in values between the subgroups that used constrained implants.…”
Section: Discussionmentioning
confidence: 84%
“…O presente estudo é um dos poucos encontrados na literatura avaliando resultados do uso de prótese constritas na população brasileira e na da América Latina. 12,13 Contrariando a hipótese prevista, o principal achado foi a observação que o uso de implantes constritos possibilita função articular e força muscular comparáveis a dos pacientes que realizaram artroplastia primária utilizando implantes convencionais com estabilização posterior. Em nossa amostra, a média do KSS funcional foi 69,80 pontos no grupo Hinge, não sendo estatisticamente distintos dos 74,23 pontos observados no grupo controle; também não encontramos diferenças nos valores entre os subgrupos que utilizaram implantes constritos.…”
Section: Discussionunclassified
“…Some studies showed excellent outcomes (10,11) , while others showed a high complication rate. In a series with a high complication rate, postoperative infection, the most frequent complication, occurred in approximately 45% of patients (12) .…”
mentioning
confidence: 99%